The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1051/jphys:01982004303053100
|View full text |Cite
|
Sign up to set email alerts
|

Star shaped polymers : a model for the conformation and its concentration dependence

Abstract: We propose a model giving the conformation of a star shaped polymer by taking into account the radial variation of the monomer concentration ϕ( r). For an isolated star when increasing r (at the centre of the star r = 0), the variation of ϕ (r) is first given by a constant value (r < f 1/2 l) then has a (r/l)-1 variation (for f1/2 / < r < f1/2 ν-1 /) and finally a (r/l)-4/3 variation (for r > f1/2 ν-1 l); wh ere f is the number of branches, N the number of monomers in a branch and ν and l are the excluded volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

101
1,474
7
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,315 publications
(1,586 citation statements)
references
References 17 publications
101
1,474
7
4
Order By: Relevance
“…The blob theory of branched polymers predicts a similar increase in R s with the number of arms (R s ∝ f 1/5 ). 26 Candau et al likewise suggested that R s should increase with the segmental density for branched polymers. 27 In contrast to the predictions of these theories for branched polymers, the relative independence of R s on generation number for arborescent 30K polymers is attributed to their hard spherelike behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The blob theory of branched polymers predicts a similar increase in R s with the number of arms (R s ∝ f 1/5 ). 26 Candau et al likewise suggested that R s should increase with the segmental density for branched polymers. 27 In contrast to the predictions of these theories for branched polymers, the relative independence of R s on generation number for arborescent 30K polymers is attributed to their hard spherelike behavior.…”
Section: Resultsmentioning
confidence: 99%
“…For aqueous dispersions of spherical micelles, which include almost all the solutions considered in this work, different models have been applied. In the case of low pH (around 2), where the PAA is mostly neutral, the Daoud Cotton model [17] was applied to fit the data. It is based on a dense core and a corona whose radial concentration decreases with a power law.…”
Section: Saxs and Sansmentioning
confidence: 99%
“…N A and star polymers. 73,74 This analogy is particularly obvious for the extreme case N A ) 1. Bug et al 24 find that in this limit eq 2.29 again holds although n j does not increase with N but rather is a decreasing function of…”
Section: Brief Review Of the Phenomenological Theories Of The Formatimentioning
confidence: 99%
“…Finally, Halperin et al 23,25,26 again exploit the analogy with star polymers 73,74 but for the case of N A , N B at finite f. They obtain a power law Unlike in eqs 2.22, 2.25, and 2.30 n j decreases with a logarithm of N B . The cmc is…”
Section: Brief Review Of the Phenomenological Theories Of The Formatimentioning
confidence: 99%